Pemberdayaan Petani dalam Pengendalian Hama Terpadu Melalui Pelatihan Rekayasa Ekologi dengan Refugia di Desa Sentang - Lisdayani, Lisdayani; Mayly, Syarifa; Adriansyah, Adriansyah; Suswati, Suswati; Munte, Sirmas; Kartika, Arie (Unri Conference Series: Community Engagement, 2024)
This service activity aims to encourage farmer to plant refugia around growth fields. Effort to increase the natural enemies population are very important to maintaining sustaibility of field ecosystem. The main problem for farmers is the lack of knowledge of farmers in using refugia plant as environmentally friendly in integrated pest management technology. The ecological engineering with refugia plants is a strategy to create habitats for natural enemies. This community service was carried out in Sentang Village with target partners, namely Bina Mangrove Farmers Group. Implementation methods are Pretest, Counseling about refugia plants, selecting suitable refugia plants species, Practical training and demonstration of ecological engineering with refugia plants, Post test. The results of this Community Service concluded that there was an increase in the farmers' knowledge and skills using refugia plant as environmentally friendly in integrated pest management technology.